Intraoperative management of recurrent leukoplakia at red zone - S Elengkumaran; C Deepak; A Emmanuel Dhiravia Sargunam; C Ravindran; Sharada T Rajan (Wolters Kluwer Medknow Publications, 2021)
Oral leukoplakia (OL) is a potentially malignant oral disorder (PMOD) that sometimes trans-form into oral squamous cell carcinoma (OSCC). OL is one of the most frequent PMODs seen in the oral cavity. The global prevalence of OL is approximately 2.6%, with its worst prognosis of undergoing a malignant transformation. Leukoplakia is clinically divided into red zones (tongue and floor of mouth) and nonred zones (buccal mucosa, palate, and soft palate) areas. The red zone areas have more potency of transforming into malignancy. Hence, patients with red zone areas need to be followed up more frequently and treated appropriately. This case report signifies the importance of treating one such case of leukoplakia at red zone area.